Using General Language Performance Measures to Assess Grammar Learning. Issue 2 (April 2020) - Eisenberg, Sarita L.
Abstract : Grammar is an important goal area for children with language impairment. The current article considers the use of General Language Performance Measures (GLPMs) to assess outcomes for this basic goal area and for 3 intermediate grammar goals that contribute to children's developing ability to construct increasingly longer and more complex sentences: production of word combinations, production of sentences with required and optional constituents, and production of complex sentences. These goals are very important because they address a significant deficit area for children with language impairment and enable these children to increase the informativeness of their utterances. Using GLPMs in addition to session data and probes enables speech–language pathologists to determine whether these forms are being incorporated into conversational speech.